Sildenafil Alleviates Murine Experimental Autoimmune Encephalomyelitis by Triggering Autophagy in the Spinal Cord - Duarte-Silva, Eduardo; Meiry da Rocha Araújo, Shyrlene; Oliveira, Wilma Helena; Lós, Deniele Bezerra; Bonfanti, Amanda Pires; Peron, Gabriela; de Lima Thomaz, Livia; Verinaud, Liana; Peixoto, Christina Alves (Frontiers in Immunology, 2021)
Multiple Sclerosis (MS) is a neuroinflammatory and chronic Central Nervous System (CNS) disease that affects millions of people worldwide. The search for more promising drugs for the treatment of MS has led to studies on Sildenafil, a phosphodiesterase type 5 Inhibitor (PDE5I) that has been shown to possess neuroprotective effects in the Experimental Autoimmune Encephalomyelitis (EAE), an animal model of MS. We have previously shown that Sildenafil improves the clinical score of EAE mice via modulation of apoptotic pathways, but other signaling pathways were not previously covered. Therefore, the aim of the present study was to further investigate the effects of Sildenafil treatment on autophagy and nitrosative stress signaling pathways in EAE. 24 female C57BL/6 mice were divided into the following groups: (A) Control - received only water; (B) EAE - EAE untreated mice; (C) SILD - EAE mice treated with 25mg/kg of Sildenafil s.c. The results showed that EAE mice presented a pro-nitrosative profile characterized by high tissue nitrite levels, lowered levels of p-eNOS and high levels of iNOS. Furthermore, decreased levels of LC3, beclin-1 and ATG5, suggests impaired autophagy, and decreased levels of AMPK in the spinal cord were also detected in EAE mice. Surprisingly, treatment with Sildenafil inhibited nitrosative stress and augmented the levels of LC3, beclin-1, ATG5, p-CREB and BDNF and decreased mTOR levels, as well as augmented p-AMPK. In conclusion, we propose that Sildenafil alleviates EAE by activating autophagy via the eNOS-NO-AMPK-mTOR-LC3-beclin1-ATG5 and eNOS-NO-AMPK-mTOR-CREB-BDNF pathways in the spinal cord.